Acute cholecystitis caused by Clonorchis sinensis - Rohela, M.; Surin, J.; Jamaiah, I.; Init, I.; Lee, S.H. (2006)
We are reporting a case of a 43-year-old Chinese male from Hong Kong, who came to see a doctor complaining of acute onset of severe upper abdominal pain. A diagnosis of acute cholecystitis was made and an emergency cholecystectomy was carried out. On opening the common bile duct, lancet-shaped worms were seen emerging from it. About 45 adult worms were collected and sent to the Department of Parasitology University of Malaya for identification. The worms were identified as Clonorchis sinensis. After the operation the patient was treated with praziquantel and he had an uneventful recovery.